Analisis Pemilihan Moda Perjalanan Penduduk Pada Perumahan Nusa Tamalanrea Indah - Emanuel Laba; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
Every movement made by the community cannot be fulfilled in one place so the community needs to go to a different place to be able to meet their needs by using means of transportation. The existence of the need for the activity ultimately prompts a person to choose the mode used. The purpose of this research is to find out the factors that influence the choice of travel mode of residents in Nusa Tamalanrea Indah Housing. Survey home interview through the dissemination of google form links to the residents of Perumahan Nusa Tamalanrea Indah is the method of data collection in this research and analysis using linear regression assisted by SPSS software. A factor that greatly influences the choice of mode in Nusa Tamalanrea Indah Housing, Makassar City is the number of working family members.